Effects of fermented feed on growth performance, serum biochemical indexes, antioxidant capacity, and intestinal health of lion-head goslings - Fu, Zhiqi; Ao, Na; Liang, Xiaoen; Chen, Jinhuang; Wang, Yuchuan; Wang, Qing; Fu, Jing; Liu, Chunpeng; Lu, Lizhi (Frontiers in Veterinary Science, 2023)
Introduction The aim of this study was to evaluate the effects of fermented feed on growth performance, antioxidant indexes and intestinal health in lion-head goslings. Methods 288 male lion-head goslings (one-day-old) were randomly divided into four groups (6 replicates per group, 12 samples per replicate): control group (basal diet) and fermented feed (FF) groups (basal diet supplemented with 2.5, 5.0 and 7.5% FF, respectively). The experimental period lasted 28 days. Results The results showed that 5.0 and 7.5% FF groups decreased feed conversion rate (FCR) when compared with the control group (p < 0.05). The 5.0% FF group reduced the activity of alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in serum; while the 7.5% FF group decreased the concentration of total cholesterol (TC), ALP and LDH activity (p < 0.05). Furthermore, the 7.5% FF group significantly increased total antioxidant capacity (T-AOC) in serum (p < 0.05); 2.5% and 5.0% FF groups significantly increased glutathione peroxidase (GSH-Px) in serum (p < 0.05); all FF groups increased the activity of superoxide dismutase (T-SOD) in serum (p < 0.05). For intestinal health, the villous height and villi/crypt ratio in jejunum were increased in all FF groups, but crypt depth was decreased (p < 0.05); The 5.0% FF groups enhanced T-AOC activity in jejunum (p < 0.05); The 2.5% and 5.0% FF groups enhanced GSH-Px activity (p < 0.05) in jejunum; All FF groups reduced malondialdehyde (MDA) level in jejunum (p < 0.05). LEfSe analysis showed that the cecum microbiota was significantly dominant in the 2.5% FF group compared to the control group including Firmicutes, Lactobacillales, Lactobacillus, and Prevotella; the flora that were significantly dominant in the 5.0% FF group compared to the control group included Bacteroidaceae, Bacteroides, Megamonas, and Prevotella; and the groups that were significantly dominant in the 7.5% FF group compared to the control group included Bacteroidota, Bacteroides, Bacteroidaceae, and Ruminococcaceae. Discussion In summary, dietary FF supplementation improved growth performance, serum biochemical parameters and antioxidant capacity of lion-head goslings, as well as improved jejunal tissue morphology and optimized intestinal flora structure. In particular, the FF addition at a dose of 7.5% was relatively more effective for lion- head goslings.